Mapping the implementation of formal cross-border patient migration from Eswatini to South Africa through the Phalala Fund: an interpretive policy analysis - Dlamini, Funwako Bakhile (Department of Public Health and Family Medicine, 2025)
The rise of pandemics and epidemics underscores the global nature of health systems, transcending national boundaries across low- and middle-income countries (LMICs). This study delves into Eswatini's health system's challenges in implementing formal cross-border patient migration to South Africa through the Phalala Fund. This is a flexible qualitative study conducted in two phases. Evidence was gathered from primary, secondary, and grey literature to conduct a scoping review and an interpretive policy analysis (IPA) on cross-border patient migration and the Phalala Fund. Key stakeholders in implementing Phalala Fund's cross-border patient migration and their influence on the policy implementation process were identified. This was key in understanding the inter-subjective meanings shared across stakeholders. In implementing Phalala Fund's cross-border patient migration, stakeholders had varied systems of meaning shaped by their values and reality judgements. Thisinfluenced stakeholder actions, priorities, resource allocation strategies, and communication approaches, which have presented various challenges in implementing Phalala Fund's cross-border patient migration. Some challenges have further strained stakeholder relations, resulting in limited negotiation power of the Government of Eswatini with South African health providers. Although regional cooperation policy frameworks of the Southern African Development Community (SADC) were seen as necessary in shaping cross-border patient migration, they do not necessarily mirror the legal and regulatory provisions that address the specific changing needs in health migration. The findings echo the importance of longer-term strategising in implementing Phalala's cross-border patient migration and recognising the complexities and varied meanings across stakeholders. Policymakers in similar contexts should consider the existing stakeholder relations and use them to strengthen the implementation of cross border patient migration. Further areas of research on 'systems overlap' is suggested